THE EFFECT OF THE GALLET PROBLEM-SOLVING MODEL ON COLLABORATIVE AND PROBLEM-SOLVING ABILITIES IN SALT HYDROLYSIS TOPIC - Siti Zharifah Najla Mehar; Dila Fairusi; Buchori Muslim (UIN Mataram, 2026)
This study aimed to determine how the Gallet problem-solving learning model affects students’ collaborative and problem-solving abilities in the salt hydrolysis topic. The Gallet model has not been widely tested on salt hydrolysis, making its effectiveness uncertain. This study used a quasi-experimental methodology with a non-equivalent control group design. The sample consisted of 35 students in class XII SAINKES 2 as the experimental class and 35 students in XII SAINKES 4 as the control class at a public high school in Bogor Regency. Essay questions measured problem-solving abilities, and observation sheets measured collaborative skills. The Mann-Whitney test analyzed the data. Findings show that the Gallet-type problem-solving model significantly improves students’ collaborative and problem-solving abilities (p < 0.05; p = 0.000). The experimental class had a higher collaborative score (21.24 out of 35) than the control class (12.68 out of 35). The experimental class average posttest score for problem-solving abilities (84.00) was higher than the control class (65.00). The experimental class had a higher N-Gain score (0.54, moderate category) than the control class (0.25, low category). Results show that the Gallet-type problem-solving model is effective for learning salt hydrolysis. ABSTRAK Penelitian ini bertujuan untuk mengetahui bagaimana model pembelajaran problem-solving Gallet memengaruhi kemampuan kolaboratif dan kemampuan memecahkan masalah siswa pada topik hidrolisis garam. Model Gallet belum banyak diujikan pada hidrolisis garam, sehingga keefektifannya belum pasti. Studi ini menggunakan metode quasi-experimental dengan desain non-equivalent control group. Sampel terdiri dari 35 siswa kelas XII SAINKES 2 sebagai kelas eksperimen dan 35 siswa kelas XII SAINKES 4 sebagai kelas kontrol di sebuah sekolah menengah negeri di Kabupaten Bogor. Kemampuan memecahkan masalah diukur dengan soal esai, sedangkan keterampilan kolaboratif diukur dengan lembar observasi. Data dianalisis menggunakan uji Mann-Whitney. Hasil menunjukkan bahwa model problem-solving Gallet secara signifikan meningkatkan kemampuan kolaboratif dan memecahkan masalah siswa (p < 0,05; p = 0,000). Kelas eksperimen memiliki skor kolaboratif lebih tinggi (21,24 dari 35) daripada kelompok kontrol (12,68 dari 35). Skor postes rata-rata kelas eksperimen untuk kemampuan memecahkan masalah (84,00) juga lebih tinggi daripada kelas kontrol (65,00). Kelas eksperimen memiliki skor N-Gain lebih tinggi (0,54, kategori sedang) daripada kelas kontrol (0,25, kategori rendah). Hasil menunjukkan bahwa model problem-solving Gallet efektif untuk pembelajaran hidrolisis garam.